Fenomena Friends With Benefits di Kalangan Mahasiswa Universitas Islam Riau Kota Pekanbaru (Studi Kasus Mahasiswa Pelaku Friends With Benefits) - Akmal Latif, Syahrul; Wastu Pratamas, Yehezkiel (SISI LAIN REALITA, 2021)
The phenomenon of  friends with benefits is a phenomenon of deviant behavior that develops in the existing social environment, especially among college students. This phenomenon is incompatible with existing social values ​​and norms because it contains deviant behavior, namely free sex. The purpose of this research is to find out what factors cause individuals to become involved and fall into this deviant behavior. So, to obtain answers to this study, researchers used qualitative methods with the type of case study research which is expected to be able to clearly describe in detail the reality that exists in the friends with benefits phenomenon. The research location that the researchers chose was the Riau Islamic University in Pekanbaru City, the choice of this location was because Riau Islamic University was one of the universities that prioritized religious values ​​in it. The conclusion of this study is that there are various kinds of factors that influence individuals to engage in deviant behavior, these factors come from the social environment which is developed into self-concepts and then used as a basis for making decisions, one of which is the decision to be involved in the relationship with friends with benefits. To minimize this deviant behavior, the role of various parties is needed, especially the role of the social environment, be it family, friendship and society as well as the college environment.